Case Report: A Novel GNB1 Mutation Causes Global Developmental Delay With Intellectual Disability and Behavioral Disorders - Da Silva, Jorge Diogo; Costa, Marta Daniela; Almeida, Bruno; Lopes, Fátima; Maciel, Patrícia; Teixeira-Castro, Andreia (Frontiers in Neurology, 2021)
Diseases of neurodevelopment mostly exhibit neurological and psychiatric symptoms that go from very mild to extremely severe. While the etiology of most cases of neurodevelopmental disease is still unknown, the discovery of underlying genetic causes is rapidly increasing, with hundreds of genes being currently implicated as disease-causing. Here, we report a clinical case of a patient with a previously undiagnosed syndrome comprising severe global developmental delay, intellectual disability, and behavioral disorders (such as attention-deficit/ hyperactivity disorder, autism spectrum disorder and recurrent bouts of aggressive behavior). After genetic testing, a pathogenic variant was detected in the GNB1 gene¸ which codes for the G-protein subunit β1. The detected variant (c.217G>A, p.A73T) has not been previously reported in any of the 58 published cases of GNB1 encephalopathy. However, it localizes to the mutational hotspot in exons 6 and 7 in which 88% of all missense mutations occur. An in silico model predicts that this mutation is likely to disrupt the WD40 domain of the GNB1 protein, which is required for its interaction with other G-proteins and, consequently, for downstream signal transduction. In conclusion, we reported an additional GNB1 encephalopathy patient, bearing a novel mutation, taking another step towards a better understanding of its clinical presentation and prospective development of treatments for the disease.